IEE Acarya Training to Enhance Learning and Life Skills: The Role of Culture in Entrepreneurial Decision-Making - Benny Agustian; Taufiq Budi Satriyo; Regina Fortunata Salim; Ina Agustini Murwani (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2026)
This study aims to develop and assess the feasibility of the IEE Acarya training model as an alternative learning method and medium for high school students to enhance learning motivation and life skills. The research applies a design thinking approach consisting of five stages: empathize, define, ideate, prototype, and test. The model integrates experiential learning and entrepreneurship-based education principles. The data were collected through literature review, observation, and feedback from pilot participants in selected schools in Jakarta. The findings show that the IEE Acarya model effectively stimulates students’ learning motivation, creativity, and problem-solving skills through game-based learning experiences. The business model developed using the Business Model Canvas demonstrates practical feasibility from educational, technological, and financial perspectives. This study contributes to the innovation of entrepreneurship education by integrating design thinking and board game–based experiential learning as a holistic framework to foster creative and life skills among youth. Keywords: Design Thinking, Experiential Learning, Entrepreneurship Education, Board Game, Life Skills